Come to the cabaret: Voices from the modern university (Journal of Applied Learning and Teaching, 2023)
This article creates and curates a sequence of cabaret songs to represent recognizable characters or types from the scholarship and literature of the modern, neoliberalised university. Using poetic enquiry as an ethnographic technique, I stand at the border of practice-based qualitative and performative research paradigms and re-imagine such figures as the ninja, the nervous wreck, the precariat, the zombie and the activist as characters in the cabaret of the modern university. The enquiry has two primary groundings: the comprehensive literature of the increasingly toxic modern university and a sociocultural critique of the Kabarett, the underground cabarets of the Weimar Republic of the 1920s and early ‘30s. The art of the cabaret involved writing and performing satirical portraits of familiar types seen in society and the world.The expressionistic era of the Kabarett was a time of decadent creativity and unashamed freedom of voice, an era that reached eventual termination after the rise of Nazism. Foregrounded by an exploration of the features of the modern university, including its corporatism, its performative audit culture, its governmentalised hegemonic regimes of truth and its climate of anxiety and fear, the study traces the origins of its types and aims to replicate aspects of their identities. The research examines both the origin stories of ninjas, nervous wrecks, zombies, precariats and activists and interprets their identities in the satiric form of subversive Kabarett songs. The findings of this study can literally be performed. The study also reaches back to medieval and Renaissance drama to examine and critique my dramatic narrative voice. The ironic eye with which I view this cabaret aligns with that of Puck/Robin Goodfellow in Shakespeare’s A midsummer night’s dream. This ironic eye examines the denizens of the neoliberalised universities and declares, “Lord, what fools these mortals be!”